sinθ = O/H
cosθ = A/H
tanθ = O/A
cosθ*tanθ = A/H * O/A = AO/AH = O/H
Therefore, sinθ = cosθtanθ = O/H
(Notes: O=opposite, A=adjacent, H=hypotenuse)
because sin(2x) = 2sin(x)cos(x)
csc θ = 1/sin θ → sin θ = -1/4 cos² θ + sin² θ = 1 → cos θ = ± √(1 - sin² θ) = ± √(1 - ¼²) = ± √(1- 1/16) = ± √(15/16) = ± (√15)/4 In Quadrant III both cos and sin are negative → cos θ= -(√15)/4
The solution is found by applying the definition of complementary trig functions: Cos (&Theta) = sin (90°-&Theta) cos (62°) = sin (90°-62°) Therefore the solution is sin 28°.
cosec(q)*cot(q)*cos(q) = 1/sin(q)*cot(q)*cos(q) = cot2(q)
cos(α) = sin(90° - α) → cos(16° + θ) = sin(90° - (16° + θ)) = sin(74° - θ) → sin(36° + θ) = cos(16° + θ) → sin((36° + θ) = sin(74° - θ) → 36° + θ = 74° - θ → 2θ = 38° → θ = 19° → θ = 19 °+ 180°n for n= 0, 1, 2, ...
Remember that tan = sin/cos. So your expression is sin/cos times cos. That's sin(theta).
Well, darling, if we square the first equation and the second equation, add them together, and do some algebraic magic, we can indeed show that a squared plus b squared equals 89. It's like a little math puzzle, but trust me, the answer is as sassy as I am.
'csc' = 1/sin'tan' = sin/cosSo it must follow that(cos) (csc) / (tan) = (cos) (1/sin)/(sin/cos) = (cos) (1/sin) (cos/sin) = (cos/sin)2
(Sin theta + cos theta)^n= sin n theta + cos n theta
The identity for tan(theta) is sin(theta)/cos(theta).
It's 1/2 of sin(2 theta) .
The fourth Across the quadrants sin theta and cos theta vary: sin theta: + + - - cos theta: + - - + So for sin theta < 0, it's the third or fourth quadrant And for cos theta > 0 , it's the first or fourth quadrant. So for sin theta < 0 and cos theta > 0 it's the fourth quadrant
You can use the Pythagorean identity to solve this:(sin theta) squared + (cos theta) squared = 1.
because sin(2x) = 2sin(x)cos(x)
The equation cannot be proved because of the scattered parts.
The derivative of (sin (theta))^.5 is (cos(theta))/(2sin(theta))
Let 'theta' = A [as 'A' is easier to type] sec A - 1/(sec A) = 1/(cos A) - cos A = (1 - cos^2 A)/(cos A) = (sin^2 A)/(cos A) = (tan A)*(sin A) Then you can swap back the 'A' with theta